Kudo Dindiang Art as Multicultural Identity of Javanese Community in Nagari Alang Lawas - Faraswatye, Monicca; Muliati, Roza (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This research discusses the phenomenon of the existence of Kudo Dindiang art in Nagari Alang Lawas, Lareh Sago Halaban District, which reflects the cultural identity of Javanese society with a multicultural environment. Kudo Dindiang art is a typical Javanese performing art inherited by immigrant communities so that it becomes a symbol of diversity as well as a community-unifying tool. This art involves magical and ritual elements, such as the phenomenon of possession (ndadi) and the attractions of the players. This research aims to analyze how the Kudo Dindiang art becomes a representation of the cultural identity of the Javanese community in Nagari Alang Lawas. The research uses descriptive and analytical qualitative methods by conducting observations, in-depth interviews, and literature reviews in order to collect true and concrete data. The theory used, namely the theory of cultural identity proposed by Stuart Hall. The results showed that the Javanese community in Nagari Alang Lawas was able to maintain its original cultural identity through the Kudo Dindiang art of fostering a sense of tolerance and cultural integration in creating social harmony in a multicultural society.